Economic and legal features of digital markets - Rastislav Funta (DANUBE: Law, Economics and Social Issues Review, 2019)
Digitization has changed economic activity in many ways. While digitization has contributed to a very dynamic development of markets and competition, concerns are also being expressed about powerful positions of some companies. The digital transformation poses new challenges for companies, consumers, politics and society. Competition policy is also required to address these developments and to adapt existing competition law, if necessary. The following analysis of digital markets showed that it is not possible, in general, to make concrete competition policy statements or even to give detailed recommendations for the antitrust analysis. The aspects are to be considered separately and in detail when examining search engines, social networks, trading platforms and other business models. On the other hand, data (and data analysis) should stand in the centre of competition law analysis due to their importance for the economic success of digital market companies.
Keywords: 330; Digital Markets; Digital Economy; Data; Competition Policy